Engineered wetlands for wastewater treatment in Sarawak: a viable and sustainable solution - Tang, Fu (School of Chemical Engineering, Engineering Campus, Universiti Sains Malaysia, 2008)
The highly efficient treatment of domestic wastewater is still in its infancy in the state of Sarawak in Malaysia. Most of the wastewater is treated primarily via the individual septic tank (IST), which is a traditional on-site and low level treatment technology. The Urban Stormwater Management Manual, which serves as a guideline for designers in Malaysia and includes recommendations for engineered wetlands is not adhered to in most places in Sarawak. One of the most promising treatment systems for residential areas in Sarawak is the engineered wetland due to its simple construction, operation and maintenance as well as sustainability. Engineered wetlands are environmentally friendly, with high aesthetic and recreational value while being an effective and sustainable means of treatment. A preliminary viability study is presented here to study engineered wetlands as a possible domestic wastewater treatment system in residential areas in Sarawak. From the study, although the operational and maintenance costs of engineered wetlands are lower than electro-mechanical systems, it is higher than ISTs. The land use of engineered wetlands is also larger compared to ISTs. However, engineered wetlands are capable of achieving higher treatment efficiency compared to ISTs, potentially achieving Standard A of the Malaysian Environmental Quality Act 1974. From the survey carried out, 50% of the respondents which include developers are unwilling to pay extra costs for centralized wastewater treatment. Engineered wetlands require larger land area which is costly in urban residential areas. 95% of the respondents feel that it is more urgent to treat stormwater compared to wastewater, since flooding problems are a concern. A total of 77% of the respondents support the concept of engineered wetlands provided the constraints are identified and overcome. To conclude, the engineered wetland is feasible as a wastewater treatment option in Sarawak, with the support of local authorities and various parties.